Effect of live-storage period and temperature on oxygen consumption rate in the cold-water sea cucumber Parastichopus tremulus - Landes, Anja M.; Sunde, Jan; Christophersen, Gyda (Frontiers in Marine Science, 2023)
Sea cucumbers are of great significance in marine ecosystems all over the world. The red sea cucumber Parastichopus tremulus is also considered commercially interesting but very little information is available on its ecology and physiology. This study aimed at investigating this North Atlantic species` oxygen demand in relation to live-storage period and temperature in an attempt to deliver some physiological puzzle pieces useful in a potential aquacultural context. Oxygen consumption rate (OCR) was measured in P. tremulus stored in a flow-through system for up to one year, and in recirculation systems at different temperatures (4, 8 and 12°C) for up to four weeks. Throughout the experimental period, biometric data were collected from the different treatment groups and a condition index (CI) calculated. The results showed that long-term storage affected OCR and CI, which increased and decreased with time, respectively. Storage at 4°C resulted in significantly lower OCR and higher CI compared to 8 and 12°C after four weeks, suggesting that 4°C may be best for maintaining body mass during short-term storage, whereas storage at 8 and 12°C may require supplementary feeding to avoid biomass loss. Data presented in this study may be useful for a range of applications, for example in a prospective aquaculture setting, for optimizing live seafood storage, but also for impact assessment and management of wild stocks.